STRATEGI KOPERASI SYARIAH DALAM MENARIK MINAT NASABAH - Imam Wahyudi (Universitas Islam Lamongan, 2019)
The purpose of this research is to find out how the efforts of syaria cooperatives in increasing the interest of customers in saving. Sharia Cooperatives are a financial services company that is developing so it requires sharia cooperative efforts to increase customer interest in saving. This research is a qualitative study using descriptive analytical methods. Qualitative research is the one in the form of words or not numbers, even if there are numbers they are in nature as a support. The results of this research are to find out: sharia cooperative's efforts in increasing customers' interest in saving, namely: The quality of services provided by syaria cooperatives is very good, the variety of products offered by syaria cooperatives, the marketing strategies of syaria cooperatives. The marketing strategies of sharia cooperatives include introducing products through non-bank financial institutions operating in the vicinity, such as UPK (Financial Management Unit) institutions in order to find out people who have surplus funds, collaborating with stakeholders such as the religious gathering formed in the working area of syaria cooperatives, youth organizations. The product socialization for government agencies, and educational institutions from kindergarten to high school level. In addition, giving bonuses to members of syaria cooperatives that have certain balances or so-called mudharabah deposit products.